Пенал для отработавшего ядерного топлива ВВЭР-1000 - Гаврилов П. М. Петр Михайлович; Кравченко В. А. Вадим Альбертович; Гамза Ю. В. Юрий Вячеславович; Бараков Борис Николаевич; Ильиных Ю. С. Юрий Сергеевич; Шафрова Н. П. Наталия Павловна
опубл. 27.11.12